Relationship Between the Ability to Detect Frequency Changes or Temporal Gaps and Speech Perception Performance in Post-lingual Cochlear Implant Users - Xie, Dianzhao; Luo, Jianfen; Chao, Xiuhua; Li, Jinming; Liu, Xianqi; Fan, Zhaomin; Wang, Haibo; Xu, Lei (Frontiers in Neuroscience, 2022)
Previous studies, using modulation stimuli, on the relative effects of frequency resolution and time resolution on CI users’ speech perception failed to reach a consistent conclusion. In this study, frequency change detection and temporal gap detection were used to investigate the frequency resolution and time resolution of CI users, respectively. Psychophysical and neurophysiological methods were used to simultaneously investigate the effects of frequency and time resolution on speech perception in post-lingual cochlear implant (CI) users. We investigated the effects of psychophysical results [frequency change detection threshold (FCDT), gap detection threshold (GDT)], and acoustic change complex (ACC) responses (evoked threshold, latency, or amplitude of ACC induced by frequency change or temporal gap) on speech perception [recognition rate of monosyllabic words, disyllabic words, sentences in quiet, and sentence recognition threshold (SRT) in noise]. Thirty-one adult post-lingual CI users of Mandarin Chinese were enrolled in the study. The stimuli used to induce ACCs to frequency changes were 800-ms pure tones (fundamental frequency was 1,000 Hz); the frequency change occurred at the midpoint of the tones, with six percentages of frequency changes (0, 2, 5, 10, 20, and 50%). Temporal silences with different durations (0, 5, 10, 20, 50, and 100 ms) were inserted in the middle of the 800-ms white noise to induce ACCs evoked by temporal gaps. The FCDT and GDT were obtained by two 2-alternative forced-choice procedures. The results showed no significant correlation between the CI hearing threshold and speech perception in the study participants. In the multiple regression analysis of the influence of simultaneous psychophysical measures and ACC responses on speech perception, GDT significantly predicted every speech perception index, and the ACC amplitude evoked by the temporal gap significantly predicted the recognition of disyllabic words in quiet and SRT in noise. We conclude that when the ability to detect frequency changes and the temporal gap is considered simultaneously, the ability to detect frequency changes may have no significant effect on speech perception, but the ability to detect temporal gaps could significantly predict speech perception.